PERANAN KEARIFAN LOKAL DALAM MENINGKATKAN WISATAWAN DI FLOATING MARKET KECAMATAN LEMBANG - Juwita, Tita; Bambang Nurcahya, Said (LPPM Politeknik Pajajaran ICB Bandung, 2023)
Lembang District is a sub-district in the West Bandung Regency area with abundant natural resources, local wisdom, and a unique attraction with a lifestyle in a mountainous environment. The Lembang area is an area rich in growth and growth. When tourism became one of the main industries for earning income, Lembang officially turned into a tourist attraction and remains so to this day. One of the tourist attractions that is very developed in the Lembang District area is the floating market. This research studies the impact of tourism activities, especially regarding community-based tourism and sustainable tourism at floating market tourist attractions. Throughout the study qualitative methods were chosen to find out the answers to the research questions. The author uses semi-structured, in-depth interviews and observations as practical methods to obtain opinions from local residents. The results found that several activities have been developed from existing resources and lifestyles, which may be in accordance with some concepts of community-based tourism and sustainable tourism, and which can be improved and developed to support environmentally friendly tourist attractions, thereby generating more income for local communities.